2014
DOI: 10.1016/j.febslet.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

A cooperative jack model of random coil‐to‐elongation transition of the FH1 domain by profilin binding explains formin motor behavior in actin polymerization

Abstract: a b s t r a c tFilopodia are essential for the development of neuronal growth cones, cell polarity and cell migration. Their protrusions are powered by the polymerization of actin filaments linked to the plasma membrane, catalyzed by formin proteins. The acceleration of polymerization depends on the number of profilin-actins binding with the formin-FH1 domain. Biophysical characterization of the disordered formin-FH1 domain remains a challenge. We analyzed the conformational distribution of the diaphanous-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…We also note that the model of mDia1‐FH1(6PRM) structure by Zhao et al . predicted a similar R g compared to our all‐atom simulations (‘ZLHL’ in Fig. ).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…We also note that the model of mDia1‐FH1(6PRM) structure by Zhao et al . predicted a similar R g compared to our all‐atom simulations (‘ZLHL’ in Fig. ).…”
Section: Resultssupporting
confidence: 75%
“…The dependence of R g on profilin occupancy for our models is slightly weaker than previously predicted by ZLHL (Fig. ).…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…A more detailed analysis may be needed to account for the effect of multiple active profilin-binding sites. Various additional factors may play a non-trivial role in actin filament polymerization, such as: differential rates of profilin binding to different sites in the FH1 domain as well as differential rates of transfer of profilin–actin to either actin protofilament as proposed by Courtemanche and Pollard [10]; cooperative effects by multiple profilins as proposed by Zhao et al [18]; and/or (transient) binding of FH1 domains to FH2 domains as suggested by Jégou et al [15]. A complication to note regarding prior experiments is that it has been difficult to demonstrate whether force is exerted equally on both FH1 domains of the formin dimer.…”
mentioning
confidence: 99%